Comparing study of electrical transport properties of bulk Y-123 synthesized by modified wet and dry synthesis methods - Yap, Siew Hong; Awang Kechik, Mohd Mustafa; Alhadei Mohamed, Arebat Ryad; Baqiah, Hussien; Chen, Soo Kien; Lim, Kean Pah; Zailani, Thareiz Hakim; Shabdin, Muhammad Kashfi; Mohd Shariff, Khairul Khaizi; Yaakob, Yazid; Mohd Zaid, Mohd Hafiz; Abdul Karim, Mohd Khalis; et al. (Elsevier, 2025)
This qualitative comparative study discusses the fabrication of bulk YBa2Cu3O7-δ (Y-123) using various modified synthesis methods, including thermal treatment, solid-state, and thermal decomposition methods in ambient conditions. The comparison analysis yielded the following findings for all synthesis methods: i) good orthorhombicity value of crystal structure (∼0.008) (ii) oxygen content close to theoretical value (∼6.8) (iii) presence of non-superconducting phases such as Y2BaCuO5 (Y-211), BaCuO2 and CuO (iv) slightly varying of Tc-onset value, ∼92 K and (v) Thermal treatment produced a sharp transition width of temperatures, ΔTc (3.2 K), while the decomposition method resulted in sharp transition widths of mean field temperatures, such as ΔTconset−MF (1.5 K), with the highest composition of the Y-123 phase (98.3 %). Additionally, the surface morphology for all synthesis methods showed different trends in compactness. The ratio of the elements contained Y:Ba:Cu in all specimens was close to the ratio of 1:2:3. The significance of promptly grinding and subjecting to a brief heat treatment process for producing high-quality Y-123 materials is emphasized in this relative analysis. The thermal decomposition method targets a novel and advanced modified dry synthesis method to prepare superior high-temperature superconductors, especially Y-123, with cost-effectiveness and time-saving benefits, while also preserving environmentally friendly practices.